Attitudes of Parliamentary Candidates towards the Politics of Memory in Post-Communist Lithuania - Matonytė, Irmina; Šumskas, Gintaras (Politologija, 2023)
The paper dwells on the longitudinal data set of Lithuanian parliamentary candidates’ views and investigates the post-communist politics of memory. The analyzed surveys are conducted in 2008, 2012 and 2016. Several hypotheses regarding the impact of time, democratic consolidation and geopolitical challenges on the national level of the politics of memory are tested, and we examine differences among party families regarding the politics of memory. The list of dependent variables of this study includes the attitudes of the parliamentary candidates and their determination to implement lustration, ban the public display of Soviet symbols and implement the claim that Russia must compensate the damage inflicted on Lithuania during the Soviet occupation. The study reveals that the politics of memory remains a matter of contention shaped by the dynamic interaction of three kinds of logic: transitional (based on the need to mark a break from the previous regime), post-transitional (encouraged by expiring early transitional conventions and re-articulated geopolitical visions), and partisan (inspired by multi-party electoral competition).
Keywords: politics of memory; parliamentary candidates; Soviet symbols; compensation from Russia; collaboration; Lithuania